Anda di halaman 1dari 13

Surds, Indices and Logarithm Surds, Indices and Logarithm

www.tutorworldonline.com

MAT 163

Surds, Indices, and Logarithms Radical


Definition of the Radical
For all real x, y > 0 , and all integers a > 0 ,
a

x = y if and only if x = y a

where a
x

is the index is the radical is the radicand.

Surds
A number which can be expressed as a fraction of integers (assuming the denominator is never 0) 5 4 is called a rational number. Examples of rational numbers are , and 2. 2 5 A number which cannot be expressed as a fraction of two integers is called an irrational number. Examples of irrational numbers are 2 , 3 7 and .
An irrational number involving a root is called a surd. Surds occur frequently in trigonometry, calculus and coordinate geometry. Usually, the exact value of a surd cannot be determined but an approximate value of it can be found by using calculators or mathematical tables. In this chapter, a means the positive square root of a while a means the negative square root of a.

General Rules of Surds


Multiplication of surds
a b = ab For example (i)

(ii) (iii)

3 12 = 3 12 = 36 = 6 32 2 = 32 2 = 64 = 8 5 5 = 5 5 = 25 = 5

1
This document is is copyrighted by www.tutorworldonline.com is is only intended forfor self study notes This document copyrighted by www.tutorworldonline.com It It solely to be used education purpose.

MAT 163 Division of surds a b= a a = b b

For example (i)

72 2 =

(ii)

72 = 36 = 6 2 45 45 5 = = 9 =3 5

These rules are useful for simplifying two or more surds of for combining them into one single surd. Note, however, that 3 + 6 3 + 6 and 6 2 6 2 which can be easily checked by a calculator; and, therefore, in general a + b a + b and a b a b .
Example 1 (i) 3 5 + 5 = (3 + 1) 5

(ii)

40 = 4 10 = 4 10 = 2 10

=4 5
Example 2 Simplify

(i) (ii)

243 12 + 2 75 50 + 8 + 32

Solution: (i) 243 12 + 2 75 = 81 3 4 3 + 2 25 3

= 81 3 4 3 + 2 25 3 = 9 3 2 3 + 10 3 = (9 2 + 10) 3
= 17 3 (ii) 50 + 8 + 32 = 25 2 + 4 2 + 16 2 = 25 2 + 4 2 + 16 2

= 5 2 + 2 2 + 4 2 = (5 + 2 + 4) 2 = 11 2
Try This 1 Simplify

(i)

27

(ii) 28 175 + 112

(iii)

5 125 8

2
This document is copyrighted by www.tutorworldonline.com It is only to be used for self study notes

MAT 163

Rationalization of the Denominator


When a fraction has a surd in its denominator, e.g.

3 , it is usual to eliminate the surd in the 2 denominator. In fact, the writing of surds in the denominators of fractions should be avoided. The process of removing this surd is called rationalizing of the denominator.

m + n and m n are specially related surds known as conjugate surds. The product of conjugate surds is always a rational number.
( m + n )( m n ) = ( m )2 ( n ) 2 = m n For example ( 9 + 5)( 9 5) = ( 9)2 ( 5) 2 = 9 5 = 4 ( 7 + 3)( 7 3) = ( 7)2 ( 3)2 = 7 3 = 4

Example 3 5 Simplify . 3
Solution: 5 5 3 = 3 3 3
= 5 3 3

Example 4
Simplify 4 . 7+ 3

Solution: 4 4 7 3 = 7+ 3 7+ 3 7 3
= 4( 7 3) 73 = 7 3

Example 5
Simplify, without using tables or calculators, the value of 1 1 . + 3 2 3+ 2

Solution: 1 1 (3 + 2) (3 2) + = + 3 2 3 + 2 (3 2)(3 + 2) (3 + 2)(3 2)

(3 + 2) + (3 2) 92 6 = 7

3
This document is copyrighted by www.tutorworldonline.com It is only to be used for self study notes

MAT 163

Try This 2 Simplify (i)


3 12

(ii)

1 3+ 7

(iii)

7 +2 7 2

Answers to Try This


1. (i) (ii)
(iii)

3 3 7

2.

(i) (ii)
(iii)

50 2

3 2 7 3 4 11 + 4 7 3

4
This document is copyrighted by www.tutorworldonline.com It is only to be used for self study notes

MAT 163

Indices
If a positive integer a is multiplied by itself three times, we get a3 , i.e. a a a = a 3 . Here a is called the base and 3, the index or power. Thus a 4 means the 4th power of a. In general, a n means the nth power of a, where n is any positive index of the positive integer a.

Rules of Indices
There are several important rules to remember when dealing with indices. If a, b, m and n are positive integers, then (1) (2)

am an = am + n am an = am n
(a m )n = a m n a m b m = ( a b) m
a a b = b
m m m

e.g.

35 38 = 313 514 53 = 511


(52 )6 = 512 35 25 = 65
5 5 3 = 3
4 4 4

e.g.
e.g. e.g.

(3)
(4)

(5)

e.g.

(6) (7)

a0 = 1
an =
1 an
m an

e.g.
1 an e.g.

50 = 1
5 3 =
1 83
2 3 8

1 53

(8) (9)

= a
n

e.g.
m n m

=38
= 3 82 = ( 3 8)2

= a = ( a)
n

e.g.

5
This document is copyrighted by www.tutorworldonline.com It is only to be used for self study notes

MAT 163 Example 1 Evaluate Solution: (i)

(ii)

1 83

(iii)

3 16 4

(iv)

25

3 2

(i)

1 1 = 3= 8 2

(ii)

1 83

=38=2

3 2

(iii)

3 4 16

= ( 16)
4

(iv)

25

=
=

1
3 25 2

= 23

=8

1 ( 25)3 1 1 = 3= 5 125

Try This 1 Evaluate each of the following without using a calculator


(i) (v)

(ii) (vi)

17

(iii) (vii)

3 49 2

(iv)
4 3

2 3
2

3 5 243

1 814

1 27

(viii)

1 4

Example 2
1 2 1

Simplify
Solution:

(i)

a3 a5 a2

(ii)

(a 3b 2 )4

(iii)

a 5 a 2 ( a 1 ) 2

(i)

1 a3

2 5 a

1 a2

(ii)

(a b )

3 2 4 34 24

(iii)

a a
5 1 a3 1 a3

1 1 2 (a )

1 2 1 + a3 5 2 7 30

=a

= =

2 a5 2 a5

a a

1 2 1 2

=a

=a b

12 8

=a =a
Try This 2 Simplify each of the following, giving your answer in index form:
(i)

1 2 1 + 3 5 2

17 30

a 3 a 4 a 2

(ii)

16a

5 2

4a

3 2

(iii)

(a 3 b 5 )15

6
This document is copyrighted by www.tutorworldonline.com It is only to be used for self study notes

MAT 163

Solving Exponential Equations


Example 3 Solve the following exponential equations (ii) (i) 2 x = 32 4 x + 1 = 0.25 Solution: (i) 2 x = 32
2 x = 25

(ii)

x = 5

4 x + 1 = 0.25 1 4x + 1 = 4 x +1 4 = 4 1 x + 1 = 1 x = 2

Try This 3 Solve the following equations:


(i) (iv) 3x = 81 5x = 1 (ii) (v) 32 x = 8 34 x = 27 x + 3 (iii) (vi) 7x = 1 49 x 4 32 x = 6

Example 4 Solve the equation 22 x + 3 + 2 x + 3 = 1 + 2 x . Solution: 22 x + 3 + 2 x + 3 = 1 + 2 x 2 x 2 x 23 + 2 x 23 = 1 + 2 x Let y = 2 x


8 y2 + 8 y = 1 + y

8 y2 + 7 y 1 = 0 (8 y 1)( y + 1) = 0 1 y = or 1 8 1 When y= 8 1 2x = 8 x 2 = 2 3 x = 3

when y = 1
2 x = 1 (inadmissible)

7
This document is copyrighted by www.tutorworldonline.com It is only to be used for self study notes

MAT 163 Try This 4 Solve the equation 32 x + 1 + 9 = 3x + 3 + 3x .

Example 5
1 If 3x 92 y = 27 and 2 x 4 y = , calculate the values of x and y. 8

Solution: 3x 92 y = 27 1 2 x 4 y = 8
From (1):

(1)
(2)

3x (32 ) 2 y = 33 3x 34 y = 33 3x + 4 y = 33 x + 4y = 3

(3)

From (2):

2 x (22 ) y = 2 x 2 2 y

1 23 = 23 (4)

2 x 2 y = 2 3 x 2 y = 3

(3) (4) :

6y = 6 y =1 x + 4(1) = 3 x = 1

Substitute y = 1 into (3):


x = 1 and y = 1 .

Try This 5 Solve the simultaneous equations

3x + y = 243 ,

22 x 5 y = 8

8
This document is copyrighted by www.tutorworldonline.com It is only to be used for self study notes

MAT 163 Answers to Try This 1. (i) (v) 2. (i)

1 7 27
a9

(ii) (vi) (ii)

1
3

(iii) (vii) (iii)


3 5

343 81

(iv) (viii)

1 4 16

4 a x=

a 5b 6

3.

(i)
(iv)

x=4

(ii) (v)

(iii) (vi)

x = 2

x=0

x=9

x=

1 2

4. 5.

x = 1 or 2

x = 4, y = 1

9
This document is copyrighted by www.tutorworldonline.com It is only to be used for self study notes

MAT 163

Logarithms
Definition: For any number y such that y = a x ( a > 0 and a 1 ), the logarithm of y to the base a is defined to be x and is denoted by log a y . Thus if y = a x , then log a y = x For example,

81 = 34 100 = 10
2

log 3 81 = 4 log10 100 = 2

Note: The logarithm of 1 to any base is 0, i.e. log a 1 = 0 . The logarithm of a number to a base of the same number is 1, i.e. log a a = 1 . The logarithm of a negative number is undefined.
Example 1 Find the value of

(i) (iii)

log 2 64 1 log 3 9

(ii) (iv)

log9 3
log8 0.25

Solution: (i) Let log 2 64 = x


64 = 2 26 = 2 x x = 6
x

(ii)

Let log 9 3 = x 3 = 9x 3 = 32 x 1 = 2x 1 x = 2

(iii)

Let log 3

1 =x 9 1 = 3x 9

(iv)

Let log8 0.25 = x 0.25 = 8 x 1 = 23 x 4 2 2 = 23 x 3x = 2 2 x = 3

32 = 3x
x = 2

10
This document is copyrighted by www.tutorworldonline.com It is only to be used for self study notes

MAT 163

Laws of Logarithms
(1) (2) log a mn = log a m + log a n
log a m = log a m log a n n

e.g.
e.g.

log3 5 + log 3 2 = log 3 10

(3)

log a m p = p log a m

e.g.

5 log3 5 + log 3 4 = log 3 4 2 log10 5 = 2 log10 5

Example 2
Without using tables, evaluate log10 41 41 + log10 70 log10 + 2 log10 5 . 35 2

Solution: 41 41 log10 + log10 70 log10 + 2 log10 5 35 2 41 41 = log10 70 52 2 35 = log10 100

= log10 102 = 2 log10 10 =2


Try This 1 Simplify 2 log 3 5 log 3 10 + 3log 3 4 .

Changing the Base of Logarithms


Logarithms to base 10 such as log10 5 and log10 ( x + 1) are called common logarithms. An alternative form of writing log10 5 is lg 5 .Common logarithms can be evaluated using a scientific calculator. Logarithms to base e such as log e 3 and log e x are called Natural logarithms or Napierian logarithms. Natural logarithms are usually written in an alternative form, for example, log e 3 is written as ln 3 . (Note: e = 2.718... )
If a, b, and c are positive numbers and a 1 , then log a b = log c b . log c a

11
This document is copyrighted by www.tutorworldonline.com It is only to be used for self study notes

MAT 163 Example 3 Find the value of log5 16 . Solution:

log5 16 =

log10 16 1.204 = = 1.722 log10 5 0.699

Try This 2 Find the value of log 4 54 .

Solving Logarithmic Equations


Example 4 Solve the equation 3x = 18 . Solution: 3x = 18 Taking logarithms to base 10 on both sides, log10 3x = log10 18 x log10 3 = log10 18 log10 18 1.2553 x= = log10 3 0.4771 = 2.631 Try This 3 Solve the equation 5 x + 1 = 30 . Example 5 Given that log10 4 + 2 log10 p = 2 , calculate the value of p without using tables or calculators.

Solution: log10 4 + 2 log10 p = 2


log10 (4 p 2 ) = 2

4 p 2 = 102 100 p2 = 4 2 p = 25 p = 5 Since p cannot be 5 because log10 (5) is not defined, p = 5 .

12
This document is copyrighted by www.tutorworldonline.com It is only to be used for self study notes

MAT 163 Try This 4 Solve the equation log 2

3x + 1 = 3. 2x 7

Example 6 Solve the equation log10 (3x + 2) 2 log10 x = 1 log10 (5 x 3) . Solution:


log10 (3x + 2) 2 log10 x = 1 log10 (5 x 3)

log10 (3 x + 2) log10 x 2 + log10 (5 x 3) = 1 (3x + 2)(5 x 3) log10 =1 x2 (3 x + 2)(5 x 3) = 101 2 x 2 15 x 9 x + 10 x 6 = 10 x 2 5x2 + x 6 = 0 (5 x + 6)( x 1) = 0 6 x = or x = 1 5
Since x cannot be negative, x = 1 .
Try This 5 Solve the equation log 2 x 2 = 4 + log 2 ( x 3) .

Answers to Try This 1. log3 160 2. 2.877 3. x = 1.113 57 4. x= 13 5. x = 4 or 12.

13
This document is copyrighted by www.tutorworldonline.com It is only to be used for self study notes